1983
DOI: 10.1111/j.1348-0421.1983.tb03589.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Escherichia coli Infection in Mice Pretreated with Corynebacterium parvum

Abstract: The contribution of activated macrophages to protection against Escherichia coli was studied in mice treated intravenously with Corynebacterium paruum 7 days before infection. C. parvum-treated mice showed increased phagocytic activity and enhanced resistance to Listeria infection. In contrast, these mice showed increased susceptibility to a subsequent challenge with E. coli that correlated closely with a reduction in the LDso of lipopolysaccharide (LPS) in these mice. The peritoneal macrophages obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It has been known that mice sensitized with Propionibacterium acnes exhibit an enhanced susceptibility to endotoxin as determined by mortality or severe hepatic injury after injection of bacterial lipopolysaccharide (LPS), the major outer membrane component of Gram‐negative bacteria [1]. An impaired resistance to infection with Escherichia coli , a Gram‐negative bacterium, was also reported [2]. In contrast to this detrimental effect, P. acnes treatment greatly enhance the protection of mice against lethal infection with Listeria monocytogenes , a Gram‐positive bacterium [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that mice sensitized with Propionibacterium acnes exhibit an enhanced susceptibility to endotoxin as determined by mortality or severe hepatic injury after injection of bacterial lipopolysaccharide (LPS), the major outer membrane component of Gram‐negative bacteria [1]. An impaired resistance to infection with Escherichia coli , a Gram‐negative bacterium, was also reported [2]. In contrast to this detrimental effect, P. acnes treatment greatly enhance the protection of mice against lethal infection with Listeria monocytogenes , a Gram‐positive bacterium [3].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, macrophages from C. parvum-treated mice have been reported to exhibit enhanced sensitivity to the toxic effects of LPS (29). Yoshikai et al (29) have reported that incubation of peritoneal macrophages from C. parvumtreated mice with concentrations of LPS which were nontoxic to macrophages from control mice leads to greater than 50% cell death by 6 h. They suggested that this effect may be at least partially responsible for the increased sensitivity of C. parvum-treated mice to the lethal effects of LPS. Ferluga et al (7) have also reported that C. parvum-treated BALB/c mice were highly susceptible to the toxic effects of LPS.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, Vogel et al (25) reported that BCG treatment of C3H/HeJ mice leads to a lowering of the 50% lethal dose for E. coli LPS from >8 mg to 282 ,ug. Similar experiments with C. parvum have revealed that treated mice exhibit enhanced sensitivity to other bacteria (29) as well as bacterial products such as LPS (3,7,29). Several authors (discussed in references 3, 21, and 29) have concluded that the macrophage may play a central role in these altered responses to LPS.…”
mentioning
confidence: 84%
“…1), it can be assumed that the reticulo-endothelial system is involved in resistance to E. coli infection. It has been doubted, whether macrophages play a distinct role in resistance to E. coli infection (Yoshikai et al 1983). These authors have even reported an increased susceptibility of mice pretreated with C. parvurn to infection with E. coll.…”
Section: Discussionmentioning
confidence: 99%